Unraveling Macroeconomic Interdependence: A Bibliometric Analysis of Aggregate Demand, Aggregate Supply, and Real GDP - Annisa Sayyid (At-Taradhi Jurnal Studi Ekonomi, 2025)
This study aims to examine how the interaction and integration between the downward-sloping AD curve and the upward-sloping AS curve works to understand how their intersection forms macroeconomic equilibrium. Shifts in the AD curve are influenced by changes in the nominal money supply, government spending, and expectations, while the AS curve is affected by short-run input cost stickiness and shifts due to nominal wage adjustments towards the natural output level (LAS). This research employs a mixed-method approach, utilizing both bibliometric analysis and a literature review. The collected data is processed and analyzed using Microsoft Excel, OpenRefine, Biblioshiny, VOSviewer 1.6.20, and RStudio. This study indicates that research related to the interdependence of aggregate demand, aggregate supply, and real GDP has experienced growth and development, focusing on macroeconomic topics such as fiscal policy, inflation, and economic growth.